Language anxiety - an important concern in language learning - Mihaljević Djigunović, Jelena (2004)
Language anxiety has become the focus of interest of SLA researchers and ELT practitioners relatively recently. Researchers have been interested in broadening their understanding of this important affective individual learner variable and in its relationship with language learning outcomes, while ELT practitioners have wondered about the ways of helping learners to overcome language anxiety. The paper addresses the phenomenon from both the point of view of foreign language anxiety and that of L1 anxiety. After defining the concept of language anxiety, which is followed by a brief critical review of the studies done in the wolrd, the author presents results of her own research into Croatian L1 speakers' anxiety when learning and using EFL and compares these to the findings of a study of the anxiety that some Croatian L1 speakers experience when using their mother tongue. Suggestions as to how to overcome both types of anxiety are made. Special attention is paid to what learners can do themselves, to what teachers can do to help as well as to what can be done at the institutional level.
Projekt MZOS
ENG